Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18632/oncotarget.17668
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol may reverse the effects of long-term occupational exposure to electromagnetic fields on workers of a power plant

Abstract: High-voltage electricity lines are known to generate extremely low-frequency electromagnetic fields (ELF-EMFs). With the process of urbanization, increasing concerns has been focused on the potentially hazardous impacts of ELF-EMF on human health, and the conclusions are controversial. Little is known about the method of prevention against ELF-EMF induced healthy problems. A total of 186 male workers with occupational exposure to high-voltage electricity lines, and 154 male subjects with insignificant exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Although there are contradictory results, EMFs largely seem to induce damage in humans [ 20 , 21 , 25 ]. The majority of studies show the relation between EMFs and the risk of many pathologies, especially cancer and neurological diseases, amongst others [ 39 ]. Moreover, exposure to EMFs seems to produce impairment in sleep as well as to generate fatigue and general discomfort [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are contradictory results, EMFs largely seem to induce damage in humans [ 20 , 21 , 25 ]. The majority of studies show the relation between EMFs and the risk of many pathologies, especially cancer and neurological diseases, amongst others [ 39 ]. Moreover, exposure to EMFs seems to produce impairment in sleep as well as to generate fatigue and general discomfort [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since 8-OHdG was evaluated as a marker for sperm infertility (Hosen et al, 2015), UD extract can be assessed for protection against radiation-induced impact on sperm quality. 8-OHdG was also reported to increase due to electromagnetic fields, which are generated by power plants or conduction cables (Zhang et al, 2017). Therefore, UD extract can also be tested in such models.…”
Section: -Ohdg/10 6 Dg For Whole Blood and Tissuementioning
confidence: 99%
“…35 In an in vivo study, lower plasma IL-1β and IL-6 were observed in 186 male workers who had long-term exposure to 5-32 000 Hz EMFs, suggesting that ELF-EMFs may affect the immune system and reduce inflammatory responses. 36 In addition, our previous study indicates that 50 Hz EMFs with a density of 100 µT decreases the rat serum level of IFN-γ, the signature cytokine for the Th1 involved in the pathogenesis of autoimmune disorders. 27 In contrast, Ikdea, et al, report that the levels of TNF-α is not significantly changed in h-PBMCs after a 6-hour exposure to 50 Hz 100-and 500-μT EMFs.…”
Section: Discussionmentioning
confidence: 95%